1998
DOI: 10.1530/eje.0.1390631
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant familial hypoparathyroidism and sensorineural deafness without renal dysplasia

Abstract: Objective: A family is described which has a unique combination of autosomal dominant hypoparathyroidism and sensorineural deafness without renal dysplasia. Case report: The proband was a male infant aged 1 month with episodes of seizures for 20 days. He was born at 35 weeks' gestation without asphyxia, weighing 2040 g. His initial calcium, phosphorus and percentage of tubular reabsorption of phosphorus were 6.8 mg/dl (normal range 8.5-10.5 mg/dl), 8.9 mg/dl (normal range 5.5-7.4 mg/dl) and 96.8% (normal range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Detailed study of chromosome 10p should be undertaken in patients with well-defined renal tract abnormality phenotypes, especially when there is associated hypoparathyroidism or deafness [3]. Various combinations of this syndrome have been reported including familial idiopathic hypoparathyroidism and progressive sensorineural deafness without renal disease [6, 8] and autosomal recessive hypoparathyroidism with renal insufficiency and developmental delay [5]. Treatment consists of treating the clinical abnormalities associated with hypoparathyroidism, deafness, and renal disease at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed study of chromosome 10p should be undertaken in patients with well-defined renal tract abnormality phenotypes, especially when there is associated hypoparathyroidism or deafness [3]. Various combinations of this syndrome have been reported including familial idiopathic hypoparathyroidism and progressive sensorineural deafness without renal disease [6, 8] and autosomal recessive hypoparathyroidism with renal insufficiency and developmental delay [5]. Treatment consists of treating the clinical abnormalities associated with hypoparathyroidism, deafness, and renal disease at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Their location within the CaSR gene is variable as 14 are localized in the extracellular domain (Pollak et al 1994, Baron et al 1996, Pearce et al 1996, De Luca et al 1997, Mancilla et al 1998, Okazaki et al 1999, Conley et al 2000, Hendy et al 2000, Tan et al 2003, six in the transmembrane helixes (Baron et al 1996, De Luca et al 1997, Watanabe et al 1998a, Hendy et al 2000 and two in the extracellular loops within the transmembrane domain (Baron et al 1996, Hendy et al 2000. Although some authors have pointed out that mutations in the transmembrane helixes might produce more severe hypocalcemia than those present in the extracellular domain (Watanabe et al 1998b), no significant relationship has been further demonstrated between mutation location and penetrance of the mutation. The Glu 604 Lys-activating mutation lies in the Cys-rich domain of the extracellular head, which seems to be required for the coupling of ligand binding to the activation of intracellular signaling pathways (Hu et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Hormone levels typically decrease to normal range (15-50 pg/mL) [9] within 10 minutes after removing the abnormal gland ( Fig. 1).…”
Section: Preoperative Localisation Of Hyperfunctioning Parathyroid Glandmentioning
confidence: 99%